2019
DOI: 10.1155/2019/2793853
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Zinc Oxide Nanorods with the Thickness of Less than or Equal to 1 μm through Zinc Acetate or Zinc Nitrate for Perovskite Solar Cell Applications

Abstract: Arrays of zinc oxide (ZnO) nanorod (NR) were fabricated in a vertical axis direction through the two-step method of seed layer’s deposition and growth of the NR. The seed layer was applied by spin coating with a three-time repetition (n) and rotational speed (v) at 3000 rpm. After the seed layer had grown, ZnO NRs were grown with a growth solution made by combining one zinc source with one hydroxide source. There were two different zinc sources, i.e., zinc acetate dehydrate and zinc nitrate hexahydrate and, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
2
1
0
Order By: Relevance
“…The previous literature on the hydrothermal synthesis process for preparing ZnO nanorods has shown that the ZnO nanorod diameter varies with the source of Zn in the deposition solution. Our results, as seen in Figure 3, show typical nanorod diameters of 40 to 50 nm, which is significantly larger than the 20 nm sizes obtained in the synthesis from nitrate solutions [29]. However, the observed diameters are consistent with some previous nitrate-based syntheses [6,19,20], and some of the shorter nanorods visible in Figure 3 do show narrow diameters of around 20 nm.…”
Section: Discussionsupporting
confidence: 89%
“…The previous literature on the hydrothermal synthesis process for preparing ZnO nanorods has shown that the ZnO nanorod diameter varies with the source of Zn in the deposition solution. Our results, as seen in Figure 3, show typical nanorod diameters of 40 to 50 nm, which is significantly larger than the 20 nm sizes obtained in the synthesis from nitrate solutions [29]. However, the observed diameters are consistent with some previous nitrate-based syntheses [6,19,20], and some of the shorter nanorods visible in Figure 3 do show narrow diameters of around 20 nm.…”
Section: Discussionsupporting
confidence: 89%
“…This occurrence is ascribed to the presence of hydrogen anions in Sn-rich environments, facilitating a shift in the Fermi level (E f ) towards the valence band maximum (VBM) and considerably increasing the doped hole concentration [58]. The N A value of 2 × 10 19 cm −3 selected in this study aligns with the optimal values previously reported at 10 19 and 7 × 10 19 cm −3 [59,60].…”
Section: Efficiency Variation Depending On Acceptor Density (N a ) Of...supporting
confidence: 78%
“…Among all the nanomaterials, metal-oxide nanostructures are the prime interest of research objectives today. For example, zinc oxide (ZnO) nanostructures including nanowires and nanorods are considered as one of the most advanced nanomaterials research areas due to their application potentials in solar cells, nanogenerators, biosensors and other nanodevices [12][13][14][15][16][17][18][19][20][21][22][23][24]. ZnO is itself a semiconductor material of having comparatively wide band gap of approximately 3.3eVwhich makes them attractive and alternatives of many other metal-oxides for short-wavelength optoelectronic applications, transparent electronics, transparent energy harvesting devices, and integrated sensors [22,[25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%